Automatic Watering System for Oil Palm Seeds - Suriyo Ardiyanto; Zulfian Azmi; Afdal Al Hafiz (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2022)
Nursery of oil palm is a period of preparing oil palm for approximately 3 months. However, in watering still using the manual method, this method still has a weakness, namely by pulling the water hose so that farmers of oil palm have to work hard and drain energy and also take a long time. From these problems, a solution was made by making an automatic palm seed watering system using the rtc module as the scheduling of the watering system and NodeMCU as the brain of the system's main process and using the blynk application as a notification output in the form of messages. As a result, the automatic watering system can work optimally if the time of the watering process has been determined and the system is able to send notifications to the blynk and display messages on the results of the watering process, with this automatic watering system it can help the work of oil palm nursery farmers.